Do International Study Programmes Pay off for Local Students? - Zhiling Wang; Francesco Pastore; Bas Karreman; Frank van Oort (Global Labor Organization (GLO), 2021)
International study programmes are increasing in number worldwide, but little is known about the impact on local students' job prospects, especially in a non-English speaking countries. Using rich administrative data from Statistics Netherlands, we analyse labour market outcomes of native graduates in master programmes of Dutch universities between 2006 to 2014 within 5 years after graduation. A coarsened exact matching analysis within cohort-university-detailed field of study group addresses the self-selection issue by generating a matched sample of students with similar characteristics. We find that graduates from international programmmes obtain a wage premium of 2.3% starting from the 1st year after graduation, ceteris paribus. The wage premium keeps increasing by about 1% every year. We investigate the mechanisms through which the wage premium operates. The wage premia can neither be explained by wage increase via cross-firm mobility, nor by faster upward mobility within a firm. Instead, evidence point towards the differential characteristics of the first job upon graduation. Graduates from international programmes are much more likely to choose large firms that have a higher share of foreign-born employees and have business of trade for the first job. They get a head start in wage level and the initial wage advantages persist in the long-run.
Keywords: I23; J24; F22; 330; international programme; native students; wage premium; coarsened exact matching